2017
DOI: 10.1016/s1875-5372(18)30048-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation Size Effect of Tungsten Single Crystal

Abstract: The load-displacement curves, elastic modulus, indent morphology, nanohardness and elastic recovery of high purity tungsten single crystal were investigated by nanoindentation and scanning probe microscopy. Results show that W (111) crystal plane undergoes elastic deformation and plastic deformation during the loading-unloading process, and the load-displacement curve does not show discontinuity, which demonstrates that cracks and brittle fracture are not formed in the indents. Moreover, the pileup behavior ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Wen et al . 17 also reported that, with the addition of Zr, the grain size in the Al-Zn-Mg-Cu alloy still grew after a prolonged homogenization process.…”
Section: Introductionmentioning
confidence: 89%
“…Wen et al . 17 also reported that, with the addition of Zr, the grain size in the Al-Zn-Mg-Cu alloy still grew after a prolonged homogenization process.…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, nanoindentation is essentially depth-sensitive: the volume range acted on by the indenter at different depths into the sample varies, potentially producing different mechanical responses and different mechanical data. Previous materials science studies have demonstrated the universality of the indentation size effect (ISE), which is manifested as the measured elastic modulus and hardness increasing with decreasing load (or indentation depth). , The measured creep behavior of metals also shows significant ISE, as the creep strain rate sensitivity ( m ) and hardness can become smaller as the indentation displacement deepens, , whereas some metallic films have exhibited the opposite behavior . Furthermore, the mechanical and creep properties of polymer materials were reported to depend strongly on the indentation loading rate, with a higher loading strain rate generally leading to higher values of hardness and lower creep strain rate sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…Atomistic simulations based on molecular dynamics (MD) can provide information about plastic deformation mechanisms, although there are limitations in some cases. These simulations are now capable of saving financial and technological resources [1][2][3][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%